Simulation Study of Building Integrated Solar Liquid PV-T Collectors - Tomas Matuska (International Journal of Photoenergy)
Influence of building integration of polycrystalline PV modules on their performance and potential for use of active liquid cooling by use of BIPV-T collectors has been investigated by simulation analysis with a detailed model. Integration of PV modules into building envelope could reduce the annual production of electricity by a rate above 5% and negatively influence lifetime due to thermal stresses induced by high operation temperatures above 100°C in the case of warm climate and above 90°C in moderate climate. Two configurations of unglazed PV-T collectors (low-tech, high-tech) and their ability to eliminate overheating of BIPV module have been discussed. Simulation study on combined heat and electricity production from given BIPV-T collectors has been presented for three typical applications (5°C: primary circuits of heat pumps; 15°C: cold water preheating; 25°C: pool water preheating). Thermal output of unglazed BIPV-T collectors is up to 10 times higher than electricity. Electricity production could be up to 25% higher than BIPV (without cooling) for warm climate and up to 15% in moderate climate.